(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In this article we will study semantics of verbs of Yenisei texts. In the study of this object will be applied historical and comparative methods. Semantics of verbs on yenisei texts, which is the ancient source of kyrgys language, and comparative study of their lexical and grammatical meanings in modern kyrgys language and their historical aspects will be studied. Actually, the category of verbs in modern kyrgys and ancient kyrgys language is the separate big part of speech with a wide range of applications. The analyses of change the form of a verbs from time and persons and their multifaceted use, was also considered. And currently, these verbs on it is these type and system, which is have not undergone change, are widely used. Morphological and semantic grammar compiled and given us by ancestors, are actual for all Turkic languages, not only for kyrgys.